Iman dan Pengaruhnya Dalam Kehidupan - Mella Novita; Indah Yulika Pratiwi; Dimas Arya Ahmadi Sormin; Zulfahmi Zulfahmi; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The purpose of this paper is to find out about the hadiths about faith and the immoral actions of believers. The method used in this research is Content Analysis, with data collection techniques using library research. So far, many people have assumed that faith lies in the realm of theology alone. Whereas on the other hand the individual and sociological domains have an important role as a form of implementation of faith. If we examine more deeply about the Qur'an and Hadith, there are many verses and texts that state that faith is closely related to charity and morals. Morals can of course be seen from the way or attitudes of humans in their daily lives, not only attitudes but can also be seen and become the human character itself. Having clear and strong faith means that our lives are directed towards one rule that we believe in and implement in life.